Endovascular approach for midaortic syndrome in an infant: A case report. (June 2021) - Kulyabin, Yuriy Y.; Gorbatykh, Artem V.; Soynov, Ilya A.; Zubritskiy, Alexey V.; Nichay, Nataliya R.; Voytov, Alexey V.
Abstract: Midaortic syndrome presenting with severe systemic blood flow obstruction in infants is often associated with significant mortality. We describe the case of a 1-year 7-month-old girl who presented with heart failure and arterial hypertension with a severely stenotic aortic segment from the T9 to L2 level. The patient underwent balloon angioplasty with implantation of the covered stent Advanta V12 OTW 9 × 59 mm (Getinge group, Sweden). The diameter of the aorta at the stiff area was 7 mm with a peak systolic pressure gradient of 12 mmHg. The patient was discharged on 3rd postoperative day with an antihypertensive (captopril) and antiplatelet (acetylsalicylic acid) drug therapy without significant pressure gradient between the upper and lower extremities. The endovascular approach does not eliminate the stenotic area completely, but avoids aggressive management of the lesion, reduces the risk of lesion-associated complications, and allows normal growth of children until surgical management is feasible. Highlights: Midaortic syndrome manifests in infants due to high-grade stenosis; Stenting is successfully used in Near-occluded aortic segments; The endovascular approach reduces the risk of lesion-associated complications.